2008
DOI: 10.1080/01930820802289391
|View full text |Cite
|
Sign up to set email alerts
|

Branching Out: Communication and Collaboration Among Librarians at Multi-Campus Institutions

Abstract: Communication and collaboration are vital aspects of 21 st century librarianship, particularly for librarians in branch and regional settings who are often separated from their system colleagues by both physical distance and administrative structures. For this study, the authors conducted an exploratory survey to examine collaboration, communication, and networking behaviors and perceptions among librarians in multi-campus academic library systems. Results of this investigative study will lead to better unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Distance was a major factor, as it often created logistical issues such as time, money, and appropriate scheduling of the event. As found in Bottorff et al’s study [ 6 ], satellite librarians were more likely to visit the parent institution than be visited by their colleagues from the parent institution. As echoed in this study, the burden often fell on the satellite librarians’ shoulders to participate without always having the proper technological or financial support.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Distance was a major factor, as it often created logistical issues such as time, money, and appropriate scheduling of the event. As found in Bottorff et al’s study [ 6 ], satellite librarians were more likely to visit the parent institution than be visited by their colleagues from the parent institution. As echoed in this study, the burden often fell on the satellite librarians’ shoulders to participate without always having the proper technological or financial support.…”
Section: Discussionmentioning
confidence: 81%
“…This study delved deeper to look for larger patterns. From this study, we have learned that Fyfe et al’s [ 1 ] themes of centralized planning and governance, local autonomy, trust, respect, and careful communication along with Bottorff et al’s [ 6 ] themes of collaboration, communication, and networking were experienced by satellite academic health sciences librarians. Our study revealed similar themes in the attitudes and perceptions of this population.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The Bottorff article (Bottorff, 2008) addresses the most important components of collaboration by searching for factors influencing cooperation among colleagues, touching only indirectly on aspects of acquisitions work. The article describes a survey wherein 13% of the responses came from acquisitions librarians, but specifics of their work are not addressed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The diagram below illustrates on the combination of the Mendeley Institutional Editions and the Mendeley platform join to a unique solution that will drive research productivity and collaboration, supported by the library and research institution. Via this model, the communication and collaboration will be part of the vital aspects in the 21st century librarianship, particularly for librarians in branch and regional settings who are often separated from their system colleagues by both physical distance and administrative structures are able to play an effective and efficient roles in supporting the research life cycle and scholarly communication too (Bottorff, Glaser, Todd, & Alderman, 2008;Ducas & Michaud-Oystryk, 2004;Taraborelli, 2011a). In addition, it forms a bridge between the information provider (librarians) and also the information seeker to use and reuse the knowledge to improve their research visibility.…”
Section: Research Collaboration In the Age Of Social Mediamentioning
confidence: 99%